Boosting CO2 electrocatalysis through electrical double layer regulations - Qun Fan; Guangxu Bao; Hai Liu; Yihan Xu; Xiaoyi Chen; Xiangrui Zhang; Kai Li; Peng Kang; Sheng Zhang; Xinbin Ma (iScience, 2024)
Summary: Interfacial investigation for fine-tuning microenvironment has recently emerged as a promising method to optimize the electrochemical CO2 reduction system. The electrical double layer located at the electrode-electrolyte interface presents a particularly significant impact on electrochemical reactions. However, its effect on the activity and selectivity of CO2 electrocatalysis remains poorly understood. Here, we utilized two-dimensional mica flakes, a material with a high dielectric constant, to modify the electrical double layer of Ag nanoparticles. This modification resulted in a significant enhancement of current densities for CO2 reduction and an impressive Faradaic efficiency of 98% for CO production. Our mechanistic investigations suggest that the enhancement of the electrical double layer capacitance through mica modification enriched local CO2 concentration near the reaction interface, thus facilitating CO2 electroreduction.